The Schizomorphism of the world of visions in Bruno Schulz’s prose - Karwowska, Marzena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
In the article, I undertake to interpret Bruno Schulz’s prose using the methodological proposals introduced in the humanities by Gilbert Durand, a French anthropologist of imagination. Based on the implemented research perspective, the aim of the hermeneutics of The Street of Crocodiles and Sanatorium Under the Sign of the Hourglass was to unveil and discuss the imagined figures which form the anthropological network of meanings. The purpose of the array of anthropological and myth-criticism research tools used for analysing and interpreting the literary works which constitute the core of Polish literature was to define the author as an imagination phenomenon that seems to fill a research gap visible in Polish Schulz studies.